Plastic behavior and fracture of aluminum and copper in torsion tests - Bressan J.D.* (2007)
Present work investigates the plastic behavior, work hardening and the beginning of plastic instabilities, of cylindrical specimens deformed by high speed cold plastic torsion tests and at low speed tensile test. The tests were carried out in a laboratory torsion test equipment and an universal tensile test machine. The tensile tests were performed at room temperature in an universal testing machine at low strain rate of 0.034/s. Experimental torsion tests were carried out at constant angular speed that imposed a constant shear strain rate to the specimen. In the tests, the rotation speed were set to 62 rpm and 200 rpm which imposed high strain rates of about 2/s and 6.5/s respectively. The torsion tests performed at room temperature on annealed commercial pure copper and aluminum. Two types of torsion specimen for aluminum were used: solid and tubular. The solid aluminum specimen curves presented various points of maximum torque. The tubular copper specimens snowed two points of maximum. Shear bands or shear strain localization at specimen were possibly the mechanism of maximum torque points formation. The work hardening coefficient n and the strain rate sensitivity parameter m were evaluated from the equivalent stress versus strain curve from tensile and torsion tests. The n-value remained constant whereas the m-value increased ten folds for aluminum specimens: from tensile test m= 0.027 and torsion test m= 0.27. However, the hardening curves were sigmoidal. © 2007 American Institute of Physics.